Penerapan Kurikulum Prototype pada Masa Pandemi Covid-19 - Sofyan Iskandar; Fya Syaikha Fatimah; Rinanda Aprillionita; Shafina Alya Arfaiza; Wanda Hamidah; Primanita Sholihah Rosmana (FONDATIA, 2022)
This paper aims to discuss the implementation of the 2013 curriculum which will be replaced by the 2022 curriculum, due to the COVID-19 pandemic, instability is one of them in the world of education. The writing method in writing this article is to use a quantitative approach. The technique used in this research is a data collection technique. Data collection techniques through a quantitative approach can be done by collecting data briefly, both in the form of tables and graphs. The results show that the existence of a new curriculum or known as a prototype curriculum which in its implementation is able to make education in Indonesia run effectively and efficiently. This can be proven from the survey results where the majority of respondents think that the prototype curriculum will be implemented effectively. However, this must also be balanced with the availability and equitable distribution of educational facilities and infrastructure, especially in the field of technology. This paper aims to discuss the implementation of the 2013 curriculum which will be replaced by the 2022 curriculum, due to the COVID-19 pandemic, instability is one of them in the world of education. The writing method in writing this article is to use a quantitative approach. The technique used in this research is a data collection technique. Data collection techniques through a quantitative approach can be done by collecting data briefly, both in the form of tables and graphs. The results show that the existence of a new curriculum or known as a prototype curriculum which in its implementation is able to make education in Indonesia run effectively and efficiently. This can be proven from the survey results where the majority of respondents think that the prototype curriculum will be implemented effectively. However, this must also be balanced with the availability and equitable distribution of educational facilities and infrastructure, especially in the field of technology.